Wilkie’s syndrome. Analysis of 150 cases of the Iberian and Ibero-American medical literature. / Síndrome de Wilkie. Análisis de 150 casos de la literatura Ibérica e Ibero-americana. - Trejo Scorza, Ezequiel; Colina Cedeño, Oscar Luis; Brito Arreaza, Edgar José; Trejo Scorza, Carlos José (Investigación Clínica, 2021)
Abstract. Willkie’s syndrome or superior mesenteric artery (SMA) syndrome is a rare cause of gastrointestinal obstruction, due to exterior compression of the horizontal part of the duodenum by the SMA. For the study of the clinical, diagnostic and therapeutic characteristics of Wilkie’s syndrome in the Iberian and Ibero-American population, we compiled the reports of 150 cases by Iberican and Ibero-American authors, and we found a predominance of cases in females over males in a ratio of 2.57: 1. Fifty percent of the cases were in patients under 20-years of age, with the highest number of cases in schoolchildren and adolescents. The most frequent symptoms were abdominal pain, vomiting and weight loss. The disease had two forms of presentation: acute with signs of high intestinal obstruction (16.47%), and chronic (83.53%). Diagnostic radiographic studies showed in of the upper gastrointestinal tract narrowing of the horizontal portion of the duodenum and delay in the transit of contrast through the gastroduodenal region, with or without gastroduodenal dilation in 85% of cases. In computed tomographic studies it was observed decreased mesenteric-aortic angle and distance. Upper endoscopic studies showed narrowing of the horizontal part of the duodenum, with or without gastroduodenal dilation in 61.90% of cases. Of the 144 patients that received treatment, 94 cases received medical treatment, with a success rate of 62.77%; and 84 cases required surgical treatment, 59.52% of these, upon admission. The most practiced surgical procedure was laterolateral duodenojejunostomy in 70.24% of cases. We concluded that Wilkie’s syndrome is an entity that results from the reduction of the mesenteric-aortic angle and distance, with two forms of presentation: acute and chronic, that required surgical treatment in 58.33% of cases. Resumen. El síndrome de Wilkie o síndrome de la arteria mesentérica (AMS) es una causa poco común de obstrucción gastrointestinal, debido a la compresión externa de la parte horizontal del duodeno por la AMS. Para el estudio de las características clínicas, diagnósticas y terapéuticas del síndrome de Wilkie en la población ibérica e iberoamericana, analizamos los reportes de 150 casos por autores ibéricos e iberoamericanos, y encontramos un predominio de casos de sexo femenino sobre el masculino en una proporción de 2,57: 1. El 50% de los casos ocurrieron en menores de 20 años, con el mayor número de casos en escolares y adolescentes. Los síntomas más frecuentes fueron dolor abdominal, vómitos y pérdida de peso. La enfermedad tuvo dos formas de presentación: aguda con signos de obstrucción del intestino superior (16,47%) y crónica (83,53%). Los estudios de diagnóstico radiográfico mostraron en el tracto gastrointestinal superior: estrechamiento de la porción horizontal del duodeno y retraso en el tránsito del contraste a través de la región gastroduodenal con o sin dilatación gastroduodenal en 85% de los casos; en tomografía computarizada: disminución del ángulo y la distancia aórtica mesentérica; y en endoscopia superior: estrechamiento de la parte horizontal del duodeno, con o sin dilatación gastroduodenal en 61,90%. De los 144 pacientes que recibieron tratamiento, 94 casos recibieron tratamiento médico, con una tasa de éxito del 62,77%; y 84 casos requirieron tratamiento quirúrgico, 59,52% de estos, al ingreso. El procedimiento quirúrgico más practicado fue la duodenoyeyunostomía laterolateral en 70,24%. Concluimos que el síndrome de Wilkie es una entidad que resulta de la reducción del ángulo y de la distancia mesentérica aórtica, con dos formas de presentación: aguda y crónica. Se requirió tratamiento quirúrgico en el 58,33% de los casos.